Advanced Ceramic and Metallic Coating and Thin Film Materials for Energy and Environmental Applications (Springer International Publishing, 2018)
This book explores the recent developments, perspectives on future research, and pertinent data from academia, industry, and government research laboratory to discuss fundamental mechanisms as well as processing and applications of advanced metallic and ceramic thin film and coating materials for energy and environmental applications. It is a platform to disseminate the latest research progress related to processing, characterization, and modelling. The authors address both thermal barrier and environmental coatings; magnetic and thermoelectric materials; and solar cell and solid oxide fuel cell materials. It is appropriate supplementary reading for students and primary reading for researchers in materials science and engineering. .